A 32 Year old Female with Recurrent Chest Infections with Dizziness - Aman, Sakib; Biswas, Palash Kumar; Hasan Chowdhury, Forhad Uddin (Journal of Medicine, 2021)
Atrial Septal Defect (ASD) is associated with repeated chest infections. Repeated chest infections, in turn, can lead to bronchiectasis and vice versa. In this case a 32 year old female presented to us with repeated chest infections. Upon thorough examination and investigation, she was found to have both ASD along with bronchiectasis. It also shows the devastating consequences of having two serious illnesses can have on a patients life, specially in low income groups. J MEDICINE 2021; 22: 155-156